OsSGL, a Novel DUF1645 Domain-Containing Protein, Confers Enhanced Drought Tolerance in Transgenic Rice and Arabidopsis - Cui, Yanchun; Wang, Manling; Zhou, Huina; Li, Mingjuan; Huang, Lifang; Yin, Xuming; Zhao, Guoqiang; Lin, Fucheng; Xia, Xinjie; Xu, Guoyun (Frontiers in Plant Science, 2016)
Drought is a major environmental factor that limits plant growth and crop productivity. Genetic engineering is an effective approach to improve drought tolerance in various crops, including rice (Oryza sativa). Functional characterization of relevant genes is a prerequisite when identifying candidates for such improvements. We investigated OsSGL (Oryza sativa Stress tolerance and Grain Length), a novel DUF1645 domain-containing protein from rice. OsSGL was up-regulated by multiple stresses and localized to the nucleus. Transgenic plants over-expressing or hetero-expressing OsSGL conferred significantly improved drought tolerance in transgenic rice and Arabidopsis thaliana, respectively. The overexpressing plants accumulated higher levels of proline and soluble sugars but lower malondialdehyde (MDA) contents under osmotic stress. Our RNA-sequencing data demonstrated that several stress-responsive genes were significantly altered in transgenic rice plants. We unexpectedly observed that those overexpressing rice plants also had extensive root systems, perhaps because transcript levels were altered for auxin- and cytokinin-associated genes. These results suggest that the mechanism by which OsSGL confers greater drought tolerance is due to the modulated expression of stress-responsive genes, higher accumulations of osmolytes, and enlarged root systems.